Probability of hotspots emergence using Consecutive Dry Days (CDD) in West Kalimantan - Dwi Purwanti Siti; Putu Okta Veanti Desak; Sucahyono Sosaidi Dedi; Adhitiansyah Daffa; Abil Nurjani Muhammad; Yuwan Purnama Fahmi; Fatahilah Raymon M. (E3S Web of Conferences, 2023)
West Kalimantan has experienced significant loss of wet primary forests in recent years. During 2017-2021, the region also faced considerable forest and land fires compared to other areas in Kalimantan. Factors such as low rainfall and prolonged drought have contributed to the occurrence of forest fire. This research was conducted using daily rainfall data at 127 observation points and hotspot data during 2012 to 2021. The research results show monthly CDD characteristics in West Kalimantan, with the highest number of CDD occurring in Kubu Raya Regency for 126 days and the lowest in Kayong Utara, Melawi, Kubu Raya, Sambas, Kapuas Hulu, Bengkayang, Mempawah, Sintang, and Pontianak City for 3 days. The hotspot distribution pattern indicates the highest number of hotspots occurring in August throughout the 10-year period. Hotspots probability varies for each CDD category: very short CDD has a probability ranging from 0.01 to 0.11, short CDD has a probability ranging from 0.03 to 0.33, moderate CDD has a probability ranging from 0.03 to 0.38, long CDD has a probability ranging from 0.00 to 0.53, very long CDD has a probability ranging from 0.00 to 0.43, and extremely long CDD has a probability ranging from 0.10 to 0.48.